Growth and significance of the private corporate sector: emerging trends - Shanta, N. (1999)
This paper seeks to answer three questions: (1) What is the significance of the private corporate sector in the economy? (2) What has been the growth of the private corporate sector relative to that of the public sector and the non-corporate sector? (3) In absolute terms has the private corporate sector in India grown? - Reproduced
Keywords: Private sector